SYSTEM FOR AUTOMATED CALCULATION OF PARAMETERS OF THE STAGE OF LAUNCHING AN UNMANNED AERIAL VEHICLE FROM A CATAPULT-TYPE LAUNCHER - BUKOVSKA, DIANA; ANTONIUK, VICTOR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
This analysis focuses on the various stages involved in launching unmanned aerial vehicles (UAV) and highlights the key considerations that must be taken into account during these stages. When launching UAV in rugged terrain without a proper runway, alternative launch mechanisms, such as a catapult-type launcher, must be developed. The use of a catapult launcher offers several advantages, including the ability to launch in confined spaces and a quick preparation time. However, the development of a launcher is a complex process that requires a comprehensive approach, involving sophisticated engineering solutions to calculate launch parameters and the flight path of the UAV. Throughout the launch process, the UAV progresses through different stages, starting from the ignition of the starting engine until it reaches the desired height and speed. It is crucial to consider various parameters that influence the trajectory of the UAV during the launch phase. The authors determined the influence of the characteristics of the engines and launcher on the trajectory of the UAV and formulated a mathematical model for calculating the speed and coordinates of movement, which have a significant impact on the flight path. A system for automated calculation of the parameters of the first stage of launching a UAV from a catapult-type launcher is proposed, this system will reduce the time for product development, as well as reduce the influence of the human factor, which will lead to a decrease in the error in calculations. To analyze the starting characteristics of the product, a catapult model was chosen, which consists of a guide, a carriage and a UAV with a starting engine. The influence of the mass of the product, the launch angle and the distribution of external forces acting on the product are taken into account, which leads to the calculation of the initial values for further design. The result of the application of the system is to obtain the parameters of the speed of movement and the position of the flying object in tabular and graphical forms